Intravenous Immunoglobulins for Refractory Status Epilepticus: A Scoping Systematic Review of the Pediatric Literature - Zeiler, F. A.; Matuszczak, M.; Teitelbaum, J.; Kazina, C. J.; Gillman, L. M. (Journal of Pediatric Neurology, 2017)
Our goal was to perform a scoping systematic review of the literature on the use of intravenous immunoglobulins (IVIGs) for refractory status epilepticus (RSE) in pediatric patients. Articles from MEDLINE, BIOSIS, EMBASE, Global Health, Healthstar, Scopus, Cochrane Library, the International Clinical Trials Registry Platform, ClinicalTrials.gov (inception to June 2016), reference lists of relevant articles, and gray literature were searched. The strength of evidence was adjudicated using both the Oxford and Grading of Recommendation Assessment Development and Education (GRADE) methodology by two independent reviewers. We identified 21 original articles. Eighty-seven pediatric patients were described as having received IVIG therapy for RSE. The mean age was 7.8 years (range: 2–17.5 years). Seizure response occurred in 14 of the 87 patients (16.1%), with 3 (3.4%) and 11 (12.6%) displaying partial and complete responses, respectively. Seventy-three of the 87 patients (83.9%) failed to display any seizure response to IVIG therapy. No complications related to IVIG therapy were recorded. The majority of patients had moderate to severe neurological deficits upon follow-up. Oxford level 4, GRADE D evidence exists to suggest little to no impact on seizure control in pediatric autoimmune RSE. Routine use of IVIG for pediatric RSE cannot be recommended at this time and should be considered experimental.
Keywords: intravenous immunoglobulins; immunoglobulin; pediatric; children; status epilepticus; refractory status epilepticus